Sisters - McPhail, David (San Diego : Harcourt,Inc., 2003)
Although two sisters are different in many ways, they are alike too--most importantly, in their love for each other.
Originally published: New York : Harcourt Brace Jovanovich, 1984.
88687
Keywords: Sisters -- Fiction